Beschouwingen rond de huizencollectie van de Vereniging Hendrick de Keyser (Bulletin KNOB, 2000)
The private Hendrick de Keyser Association, founded in 1918, now owns approximately 350 premises on the basis of which further study of the Dutch dwelling is possible. Research was not the object of the Association; its main concern was to save the premises by acquisition, restoration and responsible management. In the first decade the Association acquired 62 premises, which were restored in an austere manner. In 1928 all the houses appeared full-page in a memorial book containing 14 different contributions: Oud-Hollandse bouwkunst en haar behoud. In 1939 the Association owned 85 premises; after an introduction they were described chronologically by F.A.J. Vermeulen in the subsequent jubilee book of which reprints appeared in 1943 and 1944.After the Second World War the collection steadily increased to 170 in 1968, which induced monument conservers R. Meischke and H.J. Zantkuijl to write Het Nederlandse Woonhuis van 1300-1800. A typology of houses was made on the basis of the internal structure, paying particular attention to the woodwork of the houses, such as the timber frames, wooden beams and lower fronts. Side rooms, entresols, upstairs flats and rear annexes were described and for the first time types like the broad and the double house were discussed.After 1969 the collection of houses doubled, which gave rise to a four-volume publication, started in 1993, on the occasion of the 75th anniversary of the Association, and completed in 2000. Each volume consists of a description of related landscapes and an approximately similar number of houses. Each volume by itself is autonomous and includes a general, often thematically coloured introduction. The structure of the building trade was chosen as a main theme in an attempt at surveying architecture and technology as a unity. Through building-historical and dendrochronological research it is now possible to date the woodwork accurately, something that used to be so elusive.For the new publication the old team of the Amsterdam Bureau for the conservation of monuments was available again: Zantkuijl, Raue and Meischke, together with the young art historian Paul Rosenberg who described each house once again and added historical data. The author works out a number of conclusions in the article, such as the organisation of the building trade, the role of carpenters and bricklayers, the influence of commissioners, the guilds and the urban building practice, the trade in building materials and the role of qualified architects.